Threshold Fluence Measurement for Laser Liftoff of InP Thin Films by Selective Absorption - Jan, Antony; Reeves, Benjamin A.; van de Burgt, Yoeri; Hayes, Garrett J.; Clemens, Bruce M. (Advanced engineering materials, 2018)
We explore conditions for achieving laser liftoff in epitaxially grown heterojunctions, in which single crystal thin films can be separated from their growth substrates using a selectively absorbing buried intermediate layer. Because this highly non‐linear process is subject to a variety of process instabilities, it is essential to accurately characterize the parameters resulting in liftoff. Here, we present an InP/InGaAs/InP heterojunction as a model system for such characterization. We show separation of InP thin films from single crystal InP growth substrates, wherein a ≈10 ns, Nd:YAG laser pulse selectively heats a coherently strained, buried InGaAs layer. We develop a technique to measure liftoff threshold fluences within an inhomogeneous laser spatial profile, and apply this technique to determine threshold fluences of the order 0.5 J cm−2 for our specimens. We find that the fluence at the InGaAs layer is limited by non‐linear absorption and InP surface damage at high powers, and measure the energy transmission in an InP substrate from 0 to 8 J cm−2. Characterization of the ejected thin films shows crack‐free, single crystal InP. Finally, we present evidence that the hot InGaAs initiates a liquid phase front that travels into the InP substrate during liftoff. In epitaxial laser liftoff, the selective absorption of a bright laser pulse by a buried layer results in the separation of the thin film above it from the substrate below, as shown in the accompanying figure. The wafer can be washed and reused for growth, lowering device costs. The resulting films are single crystal and crack free.